Chitooligosaccharides improves intestinal mucosal immunity and intestinal microbiota in blue foxes - Wei, Jiali; Su, Jing; Wang, Guiwu; Li, Wei (Frontiers in Immunology, 2024)
ObjectiveGut health is critical to the health of the host. This study was conducted to investigate the effects of Chitooligosaccharides (COS) on intestinal morphology, intestinal barrier, intestinal immunity and cecum microbiota of blue foxes.MethodsSeventy-two 125-day-old blue foxes were randomly divided into basal diet (BD) group, 200 ppm COS1 (1.5 kDa) group and 200 ppm COS2 (3 kDa) group for 8 weeks.ResultsWe elucidated that dietary COS1 supplementation promoted the development of intestinal villus morphology in blue foxes. Importantly, COS1 increased the number of goblet cells in duodenum, jejunum and ileum by 27.71%, 23.67%, 14.97% and S-IgA secretion in duodenum, jejunum and ileum by 71.59% and 38.56%, and up-regulate the expression of Occludin and ZO-1 by 50.18% and 148.62%, respectively. Moreover, COS1 promoted the pro-inflammatory and anti-inflammatory balance of small intestinal mucosa, and increased the diversity of cecum microbiota of blue foxes, especially Lactobacillus_agilis and Lactobacillus_murinus, and up-regulated the signaling pathways related to polysaccharide decomposition and utilization.ConclusionHere, we present dietary COS1 (1.5 kDa) can promote intestinal villus development, enhance intestinal barrier function, regulate intestinal immune balance and cecum microbiota homeostasis.